Evaluation of strabismus surgery effects on anterior segment measurements using pentacam - Mehmet Murat; Nilay Celebi; Cetin Akpolat (Medicine Science, 2019)
To evaluate and compare preoperative and postoperative anterior segment parameters in patients who underwent unilateral or bilateral medial rectus muscle surgery.Fifty-one eyes of 30 patients were enrolled in the retrospectively designed study. Anterior segment parameters were measured via Pentacam prior to surgery and after the surgery. Besides anterior segment evaluation detailed routine ophthalmic examination was also performed for each participant. All patients had successful surgery correction. No complication was observed during follow-up period. No changes were noted in visual acuity and intraocular pressure. Statistical changes were observed in corneal astigmatism (P=0.009/0.005), corneal volume (P=0.012), and anterior chamber volume (P=0.024). Strabismus surgery might cause anterior segment parametric changes in short-term follow up, which might be reversible through the compensation process. Scheimpflug imaging is an anterior segment imaging system and these changes can be measured by Pentacam. [Med-Science 2019; 8(2.000): 316-9]